Immunologic phenotype of a child with the MEHMO syndrome - Trochanová, I; Staníková, D; Škopková, M; Haštová, K; Gašperíková, D; Staník, J; Čižnár, P (Physiological research, 2020)
MEHMO syndrome is a rare X-linked syndrome characterized by Mental retardation, Epilepsy, Hypogenitalism, Microcephaly, and Obesity associated with the defect of protein synthesis caused by the EIF2S3 gene mutations. We hypothesized that the defect in protein synthesis could have an impact on the immune system. We describe immunologic phenotype and possible treatment outcomes in patient with MEHMO syndrome carrying a frame-shift mutation (I465fs) in the EIF2S3 gene. The proband (currently 9-year-old boy) had normal IgG and IgM levels, but had frequent respiratory and urinary tract infections. On subcutaneous immunoglobulin therapy achieving supra-physiological IgG levels the frequency of infections significantly decreased in Poisson regression by 54.5 % (CI 33.2-89.7, p=0.017). The MEHMO patient had had frequent acute infections despite normal IgG and IgM serum levels and responded well to the immunoglobulin treatment.
Keywords: mutace; Microcephaly; hypogonadismus; Epilepsy; Phenotype; dítě; výsledek terapie; mikrocefalie; Obesity; lidé; pohlavní orgány; Mutation; Treatment Outcome; eukaryotický iniciační faktor 2; epilepsie; Hypogonadism; X-Linked Intellectual Disability; obezita; Male; mentální retardace vázaná na chromozom X; Child; fenotyp; mužské pohlaví; Eukaryotic Initiation Factor-2; Genitalia; Humans